Refuting the hypothesis that semaphorin‐3f/neuropilin‐2 exclude blood vessels from the cap mesenchyme in the developing kidney. Issue 12 (13th October 2017) - Munro, David A.D.; Hohenstein, Peter; Coate, Thomas M.; Davies, Jamie A.
Abstract : Background: During murine kidney development, new cortical blood vessels form and pattern in cycles that coincide with cycles of collecting duct branching and the accompanying splitting of the cap mesenchyme (nephron progenitor cell populations that "cap" collecting duct ends). At no point in the patterning cycle do blood vessels enter the cap mesenchyme. We hypothesized that the exclusion of blood vessels from the cap mesenchyme may be controlled, at least in part, by an anti‐angiogenic signal expressed by the cap mesenchyme cells.Results: We show that semaphorin‐3f (Sema3f), a known anti‐angiogenic factor, is expressed in cap mesenchymal cells and its receptor, neuropilin‐2 (Nrp2), is expressed by newly forming blood vessels in the cortex of the developing kidney. We hypothesized that Sema3f/Nrp2 signaling excludes vessels from the cap mesenchyme. Genetic ablation of Sema3f and of Nrp2, however, failed to result in vessels invading the cap mesenchyme.Conclusions: Despite complementary expression patterns, our data suggest that Sema3f and Nrp2 are dispensable for the exclusion of vessels from the cap mesenchyme during kidney development. These results should provoke additional experiments to ascertain the biological significance of Sema3f/Nrp2 expression in the developing kidney. Developmental Dynamics 246:1047–1056, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Using gene expression data from the GUDMAP database, we selected Sema3f as an anti‐angiogenic candidate gene that may exclude developing blood vessels from the cap mesenchyme (groups of nephron progenitor cells) in the murine metanephric (permanent) kidney. In the developing kidney, Sema3f is expressed in the cap mesenchyme, and its receptor, Nrp2, is expressed in endothelia that pattern in cycles around the caps in the nephrogenic zone. Genetic ablation of Sema3f and Nrp2 in mice demonstrated that they are not required for vascular exclusion from the cap mesenchyme.